Mac OS X developer's guide - Feiler, Jesse (San Diego : Morgan Kaufmann, 2002)
Mac OS X, Apple's newest operating system for the Macintosh platform, is profoundly different from its earlier versions because of its similarity to the UNIX operating system. For developers writing software for OS X this means adjusting to two new environments to create applications and to access the enhanced features of the new OS, Cocoa and Carbon. Cocoa is an object-oriented API in which all future OS X programs will be written. Carbon is a transitional technology allowing compatibility of applications written for earlier versions of the Mac OS with Mac OS X. Mac OS X Developer's Guide focuses equally on Cocoa and Carbon, guiding the reader through these technologies and showing how to write applications in both. It is the first book for Mac OS X developers written for those who are already working on applications, as well as new developers just getting started. It starts off describing the new OS and its development tools then focuses on specific programming issues, providing tips on making the transition from classic Mac OS code to Mac OS X. * A guide for developers already writing applications as well as new developers just getting started * Focuses equally on both Cocoa and Carbon environments * Provides tips on transitioning from writing code for classic Mac OS to OS X * References Apple online materials extensively, to keep developers up to speed on changes.
Preface. Introducing Mac OS X: Introduction. Architecture Overview. Frameworks and Object-Oriented Programming. The Languages of Mac OS X: Java. The Languages of Mac OS X: Objective-C. The Languages of Mac OS X: C++. The Frameworks of Mac OS X: Cocoa. The Frameworks of Mac OS X: Carbon. The Frameworks of Mac OS X: Core Foundation and Apple Class Suites. Designing for Mac OS X: Planning Your Project. The Tools of Mac OS X: Project Builder. The Tools of Mac OS X: Interface Builde. Prototyping and Testing. Developing Help and Assistance. Packaging Your Application. Managing Your Code. Writing for Mac OS X: Applications. Building Blocks and Types. Making It Happen: Events, Responders, Delegates and Notification. Visualization (Views and Windows). Interface Design and Controls. Living in a Shared Environment. Documents and Files. Managing Menus. Printing. Action! Games and Multimedia. Writing and Using Services. Scripting in Mac OS X. Writing Reusable Components. Index.
Includes index.
Keywords: Mac OS; Operating systems (Computers).; Macintosh (Computer) -- Programming; Electronic books